Hepatoprotective effects of Curcumin-Mesoporous Silica Nanoparticles on CCl 4 -induced Hepatotoxicity Wistar rats - Hadisoewignyo, Lannie; Soeliono, Ivonne; Hartono, Sandy Budi; Hestianah, Eka Pramhyrta; Mahanani, Sri Rahayu (Indonesian Journal of Pharmacy, 2019)
It has been reported that curcumin has a hepatoprotective effect, but its low solubility limited its utilization. Recently there was so many emerging research of advanced curcumin formulation, such as nanoparticles curcumin. In our previous study, curcumin has been loaded into mesoporous silica nanoparticles (C-MSN). This study was performed both to evaluate of C-MSN hepatoprotective effect in CCl4-induced rats. Sixteen rats were divided into four groups, namely normal and CCl4 control, curcumin, C-MSN group. Treatment was given according to its group for fourteen days consecutively. At day 14, three hours after the last administration, CCl4 (1,25 ml/kgBB) were administered orally. Twelve hours later the rats were sacrificed, and blood samples were drawn from their hearts. Blood serum examination result revealed that C-MSN caused a significantly lower ALT and AST than CCl4 control group (851±271 U/L vs 1734±275 U/L; 295±155 U/L vs 1348±235 U/L; p<0.05). Its effect on hepatic serum level resembled curcumin group. However, the result was not supported by histology examination which showed a higher number of necrotic hepatic cells in C-MSN group than in the curcumin group (147±9 vs 80±16; p<0.05). From this study, it can be concluded that C-MSN revealed an excellent hepatoprotective property, but it was suspected that MSN itself has the toxic effect on the liver. A further study of MSN toxicity was needed to support its safety use.